2020
DOI: 10.1136/bmj.m3513
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital cardiac arrest in critically ill patients with covid-19: multicenter cohort study

Abstract: Objectives To estimate the incidence, risk factors, and outcomes associated with in-hospital cardiac arrest and cardiopulmonary resuscitation in critically ill adults with coronavirus disease 2019 (covid-19). Design Multicenter cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
152
8
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(206 citation statements)
references
References 17 publications
16
152
8
5
Order By: Relevance
“…Our findings contrast with the uniformly poor outcomes seen in single-centre studies of IHCA in patients with COVID-19 but are consistent with those of another published multicentre IHCA study. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings contrast with the uniformly poor outcomes seen in single-centre studies of IHCA in patients with COVID-19 but are consistent with those of another published multicentre IHCA study. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 9 More recently, a multicentre observational study of 400 patients with COVID-19 who were admitted to the ICU demonstrated a 33.8% ROSC rate and a 12.0% survival to hospital discharge, with lower rates of survival in older patients. 11 The low survival rates in these studies and concern for stretched ICU resources have spurred discussions of expanded do-not-resuscitate orders for patients with COVID-19 and concern for futility of resuscitation in this population. 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayek and colleagues found that cardiac arrest is common and associated with poor survival in patients critically ill with covid-19 1…”
mentioning
confidence: 99%
“…Although the excess death rate from untreated coronary syndromes is difficult to quantify, it is likely to be substantial 4. A drop in admissions for coronary syndromes is a risk factor for increased in-hospital cardiac arrest in the covid-19 pandemic (as Hayek and colleagues present1) as well as out-of-hospital mortality3 and morbidity, leading to a predictably higher rate of heart failure in a “third wave” of this pandemic. Primary care can play a critical role by encouraging patients with symptoms compatible with coronary syndromes—infected with SARS-CoV-2 or not—to proceed urgently to receive treatment.…”
mentioning
confidence: 99%